Balancing between identities : a gay athlete's experiences in sport and exercise domains in Finland - Aulin, Valtteri (2013)
Sport is perceived to be one of the last fortresses of heteronormative and homonegative attitudes that cause psychological and social issues for LGBT (lesbian, gay, bisexual, and transgender) athletes, especially in their self-confidence and self-concept. Furthermore, these negative mindsets challenge LGBT individuals' participation in organized sport and physical activity. To offer effective consulting services, it is vital for sport psychologists to be aware of the issues that LGBT athletes might struggle with throughout their sport careers. Adopting 'queer theory' as a theoretical framework, this study strives to understand a gay male athlete's experiences in sport and physical activity in Finland, and how these experiences reflects in his sexual identity development and management, and relationships to others in sport. Autoethnography, an 'autobiographical genre of writing', and narrative analysis was utilized in this study as it enables the reader to vicariously share author's own experiences in sport and physical activity. Self-observational and self-reflective data was gathered from author's exercise and personal memory logs. Findings are presented in the form of narrative, which is constructed based on the data produced by the author. The story reveals the challenge of sexual identity development in- and outside of sport, and the constant negotiation between social and athletic identities. Interpretations of the findings are discussed with relevant theories of sexual identity development and previous LGBT research in sport. This study shows albeit there are general positive change of attitudes towards LGBT people in Finland, homosexual athletes can still have various difficulties in developing and expressing their sexual identity in organized sport and physical activity. Queer practice has a potential to confront the unequal and oppressive heteronormative constructs in sport and physical activity domains. However, more studies and stories are needed to understand the experiences of LGBT people in sport to develop programs and interventions aimed at increasing athletes' and sport practitioners' openness to LGBT athletes.